Dekonstruksi Pendekatan Nilai Moral dan Strategi Pembelajaran Humanis di Abad 21 - Suharni; Mukh. Nursikin (CV Edujavare Publishing, 2026)
This research is motivated by the phenomenon of moral degradation in the era of digital disruption triggered by the dominance of a technocentric education system. Conventional values ​​education approaches that tend to be rigid, cognitive-centered, and dogmatic have proven ineffective in equipping students with empathy and ethical awareness in the real world and cyberspace. Therefore, this research aims to deconstruct the mainstream moral values ​​approach and reconstruct it into a framework of humanist learning strategies that are relevant to the challenges of the 21st century. This research uses a qualitative approach with a library research design. Data were obtained from primary and secondary scientific literature, which were then analyzed using critical content analysis techniques. The results of the study indicate that: (1) Current moral education approaches are often trapped in the realm of knowledge (moral knowing) and ignore emotional sensitivity (moral feeling) and real actions (moral action); (2) Humanist learning strategies are contextual solutions that can be implemented through dialogical and restitution approaches, authentic teacher role modeling, and the integration of digital ethics. This study concludes that mastery of 21st Century Skills (4Cs) must be accompanied by a humanistic approach as an ethical compass. This integration is absolutely necessary so that education produces not only a technologically adept generation but also one with civility and moral integrity.